It$1 (Bs always something /s - Radner, Gilda (Sydney ; New York : Simon and Schuster, 1989)
Her characters on "Saturday Night Live" made America laugh. Her storybook marriage to actor Gene Wilder played like a match made in Hollywood heaven. But then Gilda Radner discovered she had cancer. This is the inspirational story of her struggle towards wellness- a private, personal battle in which the humor and humanity that touched millions became her most powerful weapon
Keywords: Radner, Gilda; Comedians -- United States -- Biography; Cancer -- Patients -- Biography